Training-related modulations of the respiratory hypoxic and hypercapnic response sensitivity in young elite endurance athletes - Tomiak, T.; Lusenko, O.; Mishchenko, V. (Baltic Journal of Health and Physical Activity, 2017)
The present study was performed to clarify of training-related modulations of the cardiopulmonary system (CPS) response sensitivity to a hypoxic and hypercapnia stimulus in young endurance athletes. The practical objective was to estimate a possible association between the reduction in sensitivity to respiratory homeostasis shifts and young athletes` early sports specialization.